Acellular dermal matrix allograft used alone and in combination with enamel matrix protein in gingival recession: Histologic study in dogs - De Oliveira, Cristiane Aparecida [UNESP]; Spolidório, Luís Carlos [UNESP]; Cirelli, Joni Augusto [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP] (My University, 2005)
Gingival recession was created in six mongrel dogs. The dogs were divided into two groups based on treatment: group 1 - AlloDerm only, group 2 - AlloDerm + Emdogain. The histologic results were compared. At the end of the study, the mean values were, for groups 1 and 2, respectively: 0.06 and 0.32 mm for cementum regeneration; -0.75 and -0.86 mm for bone regeneration; -2.75 and -3.11 mm for attachment level; and 4.90 and 5.51 mm for defect extent. The epithelial formation parameter was 2.88 mm in group 1 and 2.15 mm in group 2, which was a statistically significant difference. It could be concluded that Emdogain did not result in beneficial effects when associated with AlloDerm.